The Two Alternative Explosion Mechanisms of Core-Collapse Supernovae: 2024 Status Report - Noam Soker (Universe)
In comparing the two alternative explosion mechanisms of core-collapse supernovae (CCSNe), I examine recent three-dimensional (3D) hydrodynamical simulations of CCSNe in the frame of the delayed neutrino explosion mechanism (neutrino mechanism) and argue that these valuable simulations show that neutrino heating can supply a non-negligible fraction of the explosion energy but not the observed energies, and hence cannot be the primary explosion mechanism. In addition to the energy crisis, the neutrino mechanism predicts many failed supernovae that are not observed. The most challenging issue of the neutrino mechanism is that it cannot account for point-symmetric morphologies of CCSN remnants, many of which were identified in 2024. These contradictions with observations imply that the neutrino mechanism cannot be the primary explosion mechanism of CCSNe. The alternative jittering jets explosion mechanism (JJEM) seems to be the primary explosion mechanism of CCSNe; neutrino heating boosts the energy of the jittering jets. Even if some simulations show explosions of stellar models (but usually with energies below that observed), it does not mean that the neutrino mechanism is the explosion mechanism. Jittering jets, which simulations do not include, can explode the core before the neutrino heating process does. Morphological signatures of jets in many CCSN remnants suggest that jittering jets are the primary driving mechanism, as expected by the JJEM.